Zespół Noonan u 8-letniej pacjentki - opis przypadku = 8 - year - old patient with Noonan syndrome - case report - Aleksandra Grabiec; Aleksandra Szczepkowska; Piotr Osica; Anna Janas-Naze (Kazimierz Wielki University, 2016)
Grabiec Aleksandra, Szczepkowska Aleksandra, Osica Piotr, Janas‑Naze Anna. Zespół Noonan u 8-letniej pacjentki - opis przypadku = 8 - year - old patient with Noonan syndrome - case report. Journal of Education, Health and Sport. 2016;6(12):575-581. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.216473 http://ojs.ukw.edu.pl/index.php/johs/article/view/4101         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 20.12.2016.       Zespół Noonan u 8-letniej pacjentki - opis przypadku 8 - year - old patient with Noonan syndrome - case report   Aleksandra Grabiec1, Aleksandra Szczepkowska2, Piotr Osica2, Anna Janas‑Naze2   1 Studenckie Koło Naukowe przy Zakładzie Chirurgii Stomatologicznej Uniwersytetu Medycznego w Łodzi   2 Zakład Chirurgii Stomatologicznej UM w Łodzi Kierownik: dr hab. n. med. prof. nadzw. Anna Janas-Naze               Adres do korespondencji: Aleksandra Szczepkowska Zakład Chirurgii Stomatologicznej UM w Łodzi 92-213 Łódź, ul. Pomorska 251 e-mail: aleksandra.szczepkowska@gmail.com tel. 42 675 75 71           Praca finansowana przez Uniwersytet Medyczny w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001       Streszczenie: W poniższej pracy opisano przypadek zespołu Noonan u 8- letniej dziewczynki.   Słowa kluczowe: zespół Noonan, rzadkie choroby genetyczne, znieczulenia ogólne     Abstract: The article presents the case of 7 year old girl with Noonan syndrome.   Key words: Noonan syndrome, rare genetic diseases, general anesthesia